Simplify the following expression: 3(2x+7) * O 6x + 7 O 6x + 10 O 6x + 21 O 5x + 10

Question

Simplify the following expression: 3(2x+7) *
O 6x + 7
O 6x + 10
O 6x + 21
O 5x + 10

in progress 0
Thạch Thảo 6 months 2021-09-03T21:19:06+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-03T21:20:50+00:00

    the answer is c 6x+21

    0
    2021-09-03T21:21:04+00:00

    3 x 2x = 6x

    3 x 7 = 21

    6x+21

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )